Calliandra calothyrsus and Artocarpus heterophyllus as anti-parasite for Bligon Goat - Setyono, W.; Kustantinah, K.; Indarto, E.; Dono, N. D.; Zuprizal, Z.; Zulfa, I. H. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
This study investigated the nutritional potency and efficacy of tannin-containing forages as anti-parasites sources to support the performance of female Bligon goats. Fifteen female Bligon goats were divided into 3 different groups based on feeding treatments. The first group (KG) served as the control and was fed 100% king grass (dry matter basis). The second group (KGC) was fed 50% king grass and 50% Calliandra calothyrsus leaves (dry matter basis). The third group (KGA) was fed 50% king grass and 50% Artocarpus heterophyllus leaves (dry matter basis). The study showed that supplementation with tannin-containing forages could improve feed consumption and the digestibility of dry matter (DM), organic matter (OM), and crude protein (CP). The groups that received tannin-containing forages had higher body weight gains at 22.85 g/day and 29.52 g/day for KGC and KGA respectively than the control group. The anti-parasites effects were successfully indicated by the declining number of coccidian oocysts in the feces (number/gram feces), which were 3,166; 841; and 450 for KG, KGC, and KGA respectively. Tannin-containing forage supplementation could improve the consumption and digestibility of DM, OM and CP. Supplementation improved the daily body weight gain. The number of coccidian oocysts in animals receiving supplementation was also reduced. The greatest effects on fecal coccidian oocyst reduction were attained with Jackfruit leaves (Artocarpus heterophyllus) supplementation